ANALISIS YURIDIS PERAN POLRI DALAM PENANGGULANGAN TINDAK PIDANA PEMALSUAN MATA UANG TERKAIT DENGAN UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG - Ronald F. C. Sipayung; Alvi Syahrin; Suhaidi Suhaidi; Mahmud Mulyadi (Universitas Sumatera Utara, 2016)
ABSTRACT The role of Indonesian Police in coping with the criminal act of counterfeiting currency was repressively performed through the enforcement of criminal law which is the action of eradication and the same time crushing the crime by the law enforces in criminal justice system. Coping with the crime through repressive action began from the Police Department assigned its members as investigators. Law on currency has formulated the expansion of the investigators activities within the framework of proving such as the investigator has the right/authority to open the access or to check and make copies of the electronic data saved in the computer file, internet networking, optical media, as well as all others forms of electronic data storage. The investigators may seize the evidence from the owner and provider of electronic services. Besides the repressive action, pre emtive and preventive actions are also needed through the socialization and inter-sectoral coordination wuth the holders of authorities in the field of currency. Key words : Role of Indonesian Police, Criminal Act, Currency Counterfeiting.